Russian jewry 1917-1967. Ed by G.J. Aronson, J Frumkin, A.A. Goldenweiser [A. Gol'denvejzer], J.Lewitan. [With contribs of G.J. Aronson, J. Schechtman (I.B. Šechtman), S. Gringauz, a.o.]. Transl. by J. Carmichael (Yoseloff, 1969)
With index. Union of Russian Jews.